Integrated bioinformatic analysis and experimental validation for exploring the key molecular of brain inflammaging - Du, Zhixin; Wang, Yaohui; Yang, Liping; Zhang, Tong; Jiang, Yu; Zhang, Zhenqiang (Frontiers in Immunology, 2023)
Integrating bioinformatics and experimental validation to explore the mechanisms of inflammaging in the Brain.Method: After dividing the GSE11882 dataset into aged and young groups, we identified co-expressed differentially expressed genes (DEGs) in different brain regions. Enrichment analysis revealed that the co-expressed DEGs were mainly associated with inflammatory responses. Subsequently, we identified 12 DEGs that were related to the inflammatory response and used the DGIdb website for drug prediction. By using both the least absolute shrinkage and selection operator (LASSO) and random forest (RF), four biomarkers were screened and an artificial neural network (ANN) was developed for diagnosis. Subsequently, the biomarkers were validated through animal studies.Then we utilized AgeAnno to investigate the roles of biomarkers at the single cell level.Next, a consensus clustering approach was used to classify the aging samples and perform differential analysis to identify inflammatory response-related genes. After conducting a weighted gene co-expression network analysis (WGCNA), we identified Key Molecular of Brain Inflammaging the genes that are correlated with both four brain regions and aging. Wayne diagrams were used to identify seven inflammaging-related genes in different brain regions.Finally, we performed immuno-infiltration analysis and identified macrophage module genes.